The Effect of Product Innovation, Location, and Service Quality on the Competitive Advantage of Senusa Coffeeshop in Pekanbaru City - Suseno, Novri Irfan Nur; Samsir, Samsir; Asrilsyak, Sharnuke; Syamsuri, Abd. Rasyid; Berampu, Lailan Tawila (Pusat P2M Politeknik Negeri Batam, 2025)
The Senusa Coffee Shop on Jalan Bangau Sakti Pekanbaru is where this study was carried out. The purpose of this study is to ascertain how Senusa Coffee Shop Jalan Bangau Sakti’s competitive advantage is impacted by product innovation, location, and service quality. All patrons of Senusa Coffee Shop on Jalan Bangau Sakti make up the population of this study. With a sample of 385 customers, this study employed the incidental sampling technique. Product innovation, location, and service quality are the independent factors under investigation. Where the dependent variable is a competitive advantage. The Structural Equation Modeling-Partial Least Square (SEM-PLS) analytical approach is used in this study. The study’s findings indicate that at Senusa Coffee Shop Jalan Bangau Sakti, product innovation significantly boosts competitive advantage, location significantly boosts competitive advantage, and service quality significantly boosts competitive advantage. The R-Square value of 90,5% demonstrates the extent of the relationship between the variables of product innovation, location, and service quality.